IDENTIFICATION OF UTERIN MILK PROTEIN (UTMT) GENE IN BALI CATTLE USING DIRECT SEQUENCING - Jakaria, J.; Saputra, F.; Paramitasari, K. A.; Agung, P. P.; Maskur, M. (Diponegoro University, 2016)
The objective of this research was to identify diversity of exon 5 UTMP gene fragment in Bali cattle using direct sequencing. The total 60 blood samples of Bali Cattle derived from BPTU Bali in Bali siland (20 heads), BPTU Serading in Sumbawa island (20 heads) and Village Breeding Center in Barru District South Sulawesi (20 heads) were used to evaluate their genetic diversity at exon 5 UTMP gene. The forward and reverse data sequences were analyzed using Bioedit program and alignment analysis was carried out using MEGA5 program. Meanwhile haplotype analysis was performed by DnaSPv5 program. The result showed that partial sequences in exon 5 UTMP gene had 16 haplotypes with the highest number of haplotypes ware found in VBC Barru district South Sulawesi (8 haplotypes). Moreover, the highest average of haplotype (h) and nucleotide (p) diversity were found in VBC Barru district South Sulawesi were 0.7949 and 0.0016, respectively. In addition, minisatellite insersion was found in exon 5 UTMP gene fragment on Bali cattle which are consist of 5'-CCA GTC ATG AAG AAG GCA GAG GTC GTC GTG CCG GCG AAA-3'. According to our results, haplotype and minisatellite variation in exon 5 UTMP gene fragment can be used as a candidate genetic marker specific for reproductive trait in the Bali cattle and for its strategy breeding program in the future.